Ekspresi Fatis dalam Obrolan Orang Jepang di Eneos Saijo Inta Service Station Hiroshima - Sadewo, Leo; Haristiani, Nuria (Vocational College of Diponegoro University, 2023)
The study is to describe the use of phatic expressions in Japanese Line application chats at Eneos Saijo inta service station Hiroshima. The research uses a descriptive method and a qualitative approach and uses scanning and recording techniques to process data in the form of message history in Line chats written directly by Japanese people. The data was collected from the message history of the data period from May 01, 2020 to May 30, 2021 in Hirosima Prefecture. Based on the findings of the data, phatic expressions are used as a means of small talk by speech partners to speakers. The use of phatic expressions is used as a form of familiarity, attention and politeness before leading to the main topic of conversation. Phatic expressions are similiar with the concept of tatemae which focuses on harmonizing social relationships including greetings, manners, and politeness. The use of phatic expressions in communication is very important as a means of opening and closing human interaction (human relation) that indicates the establishment of social relations between individuals.